Acute mercury exposition of virgin, pregnant, and lactating rats: Histopathological kidney and liver evaluations. Issue 5 (11th October 2016) - Oliveira, Vitor Antunes; Favero, Gaia; Stacchiotti, Alessandra; Giugno, Lorena; Buffoli, Barbara; de Oliveira, Claudia Sirlene; Lavazza, Antonio; Albanese, Massimo; Rodella, Luigi Fabrizio; Pereira, Maria Ester; Rezzani, Rita
ABSTRACT: This work investigated the effects of mercury chloride (HgCl2 ) acute exposure on virgin, pregnant and lactating rats by determination of renal and hepatic morphological and ultrastructural parameters and the expression of oxidative stress and stress tolerance markers, due to kidney and liver are the organs that more accumulate inorganic mercury. Adult Wistar rats virgin (90 days old), pregnant (18 th gestation day) and lactating (7 th lactation day) were injected once with HgCl2 (5 mg/kg) or saline (controls). We observed that HgCl2 exposure of virgin rats caused significant inflammatory infiltration and severe morphological variations, like glomeruli atrophy, dilatation of Bowman's capsule, tubular degeneration and hepatocytes alteration. Moreover, virgin rats presented mitochondrial modification, important oxidative stress and increase in stress tolerance proteins at both kidney and liver level, compared with virgin controls. In detail, virgin rats exposed to HgCl2 presented significantly elevated level of inducible nitric oxide synthase, heat shock protein 27 and glucose regulated proteins 75 expressions at both renal tubular and hepatocytes level, respect untreated virgin rats. Interestingly, pregnant and lactating rats exposed to HgCl2 presented weak renal and liver morphological alterations, showing weak inflammatory infiltration and no significant difference in structural mitochondrial transmembrane protein, oxidative stress markers and stress tolerance proteins expressions respect controls (virgin, pregnant and lactating rats). Although, both control and HgCl2 ‐exposed pregnant and lactating rats showed renal glomeruli greater in diameter respect virgin rats. In conclusion, we believe that virgin rats are more sensitive to HgCl2 toxicity respect pregnant and lactating rats. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 1500–1512, 2017.